ANALISIS FORECAST DAN VALUATION MANAJEMEN FIXED ASSET PADA PERUSAHAAN IDX30 BURSA EFEK INDONESIA - Martias, Andi; Rachmawati, Susan; Sudirja, Sudirja; Wahyuhening F, Firstianty (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
Every company has fixed assets that are used in its business operations. This article aims to investigate the problem, which stems from fixed assets that affect the profitability and efficiency of asset management. This study seeks to identify the impact of forecasting and valuation in fixed asset accounting through several objectives. Fixed asset management is the process of recording and tracking long-term assets throughout their entire life cycle, from acquisition to disposal. Companies must keep accurate records to ensure compliance with accounting standards and reporting requirements. The results of the analysis are known Overall, the fixed asset management of manufacturing companies shows satisfactory performance. Effective debt and equity balances, efficient utilization of investments, loans, and down payments, and impressive profitability demonstrate a well-managed approach.